Changing the Story: Indigenous Youth Belong in Post-Secondary Education - First Rider, Wanda; Hanson, Aubrey Jean; Houle, Angela; McCallum, Patricia; Miles, Teresa M.; Plante, Maureen; Spring, Erin (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
This article describes a collaboration between an urban school board and a faculty of education aimed at supporting Indigenous youth transitions to post-secondary education. Drawing upon strengths-based approaches including wise practices, we offer a model for how postsecondary transition events can illuminate pathways for young people to see that they belong in higher education. We highlight the importance of connecting with Elders, hearing from successful Indigenous speakers, and seeing campus. The theme of our event reiterates to Indigenous youth that they have a story and that they can take the next steps to a new beginning in post-secondary education.